2002
DOI: 10.1016/s0140-3664(01)00408-x
|View full text |Cite
|
Sign up to set email alerts
|

The potential costs and benefits of long-term prefetching for content distribution

Abstract: This paper examines the costs and potential benefits of long-term prefetching for content distribution. In contrast with traditional short-term prefetching, in which caches use recent access history to predict and prefetch objects likely to be referenced in the near future, long-term prefetching uses long-term steadystate object access rates and update frequencies to identify objects to replicate to content distribution locations. Compared to demand caching, long-term prefetching increases network bandwidth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 20 publications
0
70
0
Order By: Relevance
“…Several studies have demonstrated the effectiveness of prefetching in addressing the limitations of passive caching (e.g., [14], [17], [22], [23], [27], [31], [32], [35], [42], [46], [49]). Prefetched documents may include hyperlinked documents that have not been requested yet as well as dynamic objects [37], [42].…”
Section: A Motivation and Related Workmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of prefetching in addressing the limitations of passive caching (e.g., [14], [17], [22], [23], [27], [31], [32], [35], [42], [46], [49]). Prefetched documents may include hyperlinked documents that have not been requested yet as well as dynamic objects [37], [42].…”
Section: A Motivation and Related Workmentioning
confidence: 99%
“…3. The paper also proves that the algorithms based on Good Fetch [14] and on the APL characteristic [9], although using different criteria, are equivalent in terms of their choice of objects selected for prefetching.…”
Section: ¦ ¥mentioning
confidence: 69%
“…This criterion was first proposed by Jiang et al [9] as a performance metric in terms of both hit rate and bandwidth usage. Jiang et al [9] compared different algorithms, i.e., Prefetch by Popularity [12], Good Fetch [14], APL characteristic [9], and Lifetime [9], using this criterion, but did not give any algorithm to optimize this criterion. 2.…”
Section: ¦ ¥mentioning
confidence: 99%
See 2 more Smart Citations